The contribution of municipal commonage to local people's livelihoods in small South African towns - Davenport, Nicholas Ashbury (Rhodes University, Faculty of Science, Department of Environmental Science, 2009)
To redress past discrepancies in land tenure, the ANC government acknowledged that land needs to be made accessible to the previously disadvantaged, announcing that commonage would be a pillar of their land reform programme. Municipal commonage is land granted by the state to municipalities for urban households to use. Presently many urbanites in South Africa seek a livelihood from commonage. However, there has been no livelihood valuation of the contribution commonage makes to previously disadvantaged households. Thus there is a need to calculate the benefits of the commonage programme. Through a two phase approach, this thesis investigated firstly, the proportion of township households which use commonage; and the main characteristics of those households. Secondly, the thesis looks at the extent to which commonage contributes to users' livelihoods and the dominant livelihood strategies pursued by user households. Data was collected for three towns in the Eastern Cape province of South Africa; Bathurst, Fort Beaufort, and Grahamstown. Firstly it was found that between 27-70% of households used commonage, with the largest town having the lowest proportion of users, and vice versa for the smallest town. In terms of household characteristics, each study town was unique. Both Bathurst and Grahamstown user households were poorer than non-using households, however all Fort Beaufort households were considered poor. To assess the benefits of the commonage programme, the marketed and non-marketed consumptive direct-use values of land-based livelihoods on commonage were calculated via the 'own reported values' method. Commonage contributions to total livelihoods ranged between 14-20%. If the contributors from commonage were excluded, over 10% of households in each study town would drop to living below the poverty line. Additionally, commonage was being used productively, with the productivity at each study town being worth over R1 000 per hectare and over R4.7 million per commonage. Finally, a typology of subsistence/survivalist commonage users is presented, with four types being identified. Overall, results suggest that commonage use has increased over the last decade. Moreover, due to food inflation and urbanisation the use of commonage is expected to increase further, highlighting the need for holistic commonage management plans to be created, which should include strategies such as sustainable grazing regimes and natural resource management.
Keywords: Land tenure -- South Africa; Land reform -- South Africa; Property -- South Africa; Property rights -- South Africa; Commons -- South Africa -- Eastern Cape; Natural resources, Communal -- Management -- South Africa -- Eastern Cape; Rural development -- South Africa -- Eastern Cape; Households -- Economic aspects -- South Africa -- Eastern Cape